Visualizing anthropology - Grimshaw, Anna; Ravetz, Amanda (Intellect, 2005)
Questions of vision and knowledge are central to debates about the world in which we live. Developing new analytical approaches toward ways of seeing is a key challenge facing those working across a wide range of disciplines. How can visuality be understood on its own terms rather than by means of established textual frameworks? Visualizing Anthropology takes up this challenge. Bringing together a range of perspectives anchored in practice, the book maps experiments in the forms and techniques of visual enquiry. The origins of this collection lie in visual anthropology. Although the field has.